Criminal law policy about KPK authorities in the perspective of criminal action in corruption in Indonesia - Ilham, Ilham (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Criminal law policy of the authority of the Corruption Eradication Commission the authority associated with the Corruption Eradication Commission (KPK) is the state agency that are unconstitutional, although not spelled out in the state constitution is the 1945 Constitution. Corruption eradication commission (KPK) was formed to look at the nature of the corruption itself is an extraordinary crime, so it requires an independent institution to fight corruption in Indonesia. Background The Commission is not due to the formation of the constitutional design rigidly interpreted, but rather incidental issues in the country and the common will of the people of Indonesia to combat corruption. Position of the Commission as a state agency is independent and free from the influence of any power, it is meant for combating corruption Commission did not get the intervention of any party. The establishment of the Commission was also a response to the ineffectiveness of the law enforcement agency performance so far in combating corruption, which impressed protracted in handling even indicated there was an element of corruption in the handling of his case. The authority granted by the Act prosecution to the Commission under the authority of the legitimate .The authority of the Commission is constitutional, it is reinforced by a number of decisions of the Supreme constitution..